Brightly Burning - Lackey, Mercedes (New York : Distributed by Penguin Putnam, 2000)
Lavan, brought to the capital city of Haven against his will, suffers humiliation and beatings at the hands of his classmates until his rage transforms him into something fearsome and powerful--with training, he will become the most notorious Herald in Valdemar's history.
Booklist starred.
Library Journal.
Voice of Youth Advocates (V.O.Y.A.).
Young Adult
Keywords: Extrasensory perception -- Fiction; Valdemar (Imaginary place) -- Fiction; Bildungsromans; Extrasensory perception -- Fiction; Valdemar (Imaginary place) -- Fiction; Fantastic fiction